2019
DOI: 10.48550/arxiv.1904.07224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 2019 Discovery of a Meteor of Interstellar Origin

Abstract: The first interstellar object, 'Oumuamua, was discovered in the Solar System by Pan-STARRS in 2017, allowing for a calibration of the abundance of interstellar objects of its size ∼ 100 m. One would expect a much higher abundance of smaller interstellar objects, with some of them colliding with Earth frequently enough to be noticeable. Based on the CNEOS catalog of bolide events, we identify the ∼ 0.45m meteor detected at 2014-01-08 17:05:34 UTC as originating from an unbound hyperbolic orbit with 99.999% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Another potential constraint for this distribution is the number density n CNEOS = 10 6 +0.75 −1.5 au −3 of r CNEOS 0.45 m interstellar objects implied by the candidate interstellar meteor identified from the Center for Near-Earth Object Studies (CNEOS) bolide catalog in Siraj & Loeb (2019). We note that Devillepoix et al (2018) reported that the United States government sensors used to discover this object are generally unreliable for orbit calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Another potential constraint for this distribution is the number density n CNEOS = 10 6 +0.75 −1.5 au −3 of r CNEOS 0.45 m interstellar objects implied by the candidate interstellar meteor identified from the Center for Near-Earth Object Studies (CNEOS) bolide catalog in Siraj & Loeb (2019). We note that Devillepoix et al (2018) reported that the United States government sensors used to discover this object are generally unreliable for orbit calculations.…”
Section: Resultsmentioning
confidence: 99%
“…(35) Dohnanyi (1969) made a theoretical argument for taking α = 2.5 for material in collisional equilibrium in protoplanetary disks, and this appears to be broadly representative of small-body populations in the solar system (Jedicke et al 2002). Attempts have also been made to determine the exponent α for interstellar objects empirically, based on direct measurements of interstellar dust by the Ulysses and Galileo spacecraft (Landgraf et al 2000), and optical and radar detections of meteors identified as interstellar (Taylor et al 1996;Baggaley 2000;Meisel et al 2002;Weryk & Brown 2004;Hajduková 2008Hajduková , 2011Siraj & Loeb 2019a). On the basis of the Ulysses and Galileo data alone, Landgraf et al (2000) estimated α = 3.3.…”
Section: Frequency Of Encountersmentioning
confidence: 99%
“…On the basis of the Ulysses and Galileo data alone, Landgraf et al (2000) estimated α = 3.3. Most recently, Siraj & Loeb (2019b) arrived at α = 3.41 ± 0.17 in an analysis incorporating 'Oumuamua and the bolide meteor CNEOS 2014-01-08 (Siraj & Loeb 2019a), which is unique among meteors identified as interstellar because of its relatively large size, estimated at 0.45 m.…”
Section: Frequency Of Encountersmentioning
confidence: 99%
“…'Oumuamua was the first interstellar object discovered in the Solar system (Meech et al 2017;Micheli et al 2018). Its discovery was followed by interstellar comet Borisov (Guzik et al 2020), and preceded by interstellar meteor CNEOS-2014-01-08 (Siraj & Loeb 2019a). The Vera C. Rubin Observatory's Legacy Survey of Space and Time (LSST) 1 will greatly increase the cadence of interstellar object discovery to a rate of several per year for 'Oumuamua-size objects (Rice & Laughlin 2019).…”
Section: Introductionmentioning
confidence: 99%